2012
DOI: 10.1111/j.1750-2659.2012.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the hospitalized patients with 2009 pandemic influenza A (H1N1) in Santa Fe, Argentina

Abstract: Background  During 2009 occurred the emergence and global spread of a novel influenza A (H1N1) virus. We describe the clinical and epidemiologic features of hospitalized patients who survived and patients who died because of pandemic 2009 influenza A (H1N1) infection reported in Santa Fe, Argentina, from May to July 2009. Methods  Using medical charts, we collected data on 242 patients who were hospitalized with confirmed laboratory results (defined as positive by specific PCR for pandemic 2009 influenza A H1N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 9 chronic conditions influencing the severity of MERS-CoV such as diabetes, hypertension, obesity, and CAD/CVD were also noted to have similar effects in other respiratory illnesses such as influenza 15 and H1N1. [16][17][18] In contrast, comorbidities such as immunodeficiency and HIV were reported to be in low prevalence in severe MERS-CoV cases (range: 0-5%) 1,3 compared, for example, to their rates in severe H1N1 cases (range: 3-32%). 16,19 Metabolic syndrome-related conditions such as diabetes, hypertension, CAD/CVD and obesity complications.…”
Section: Discussionmentioning
confidence: 74%
“…A c c e p t e d M a n u s c r i p t 9 chronic conditions influencing the severity of MERS-CoV such as diabetes, hypertension, obesity, and CAD/CVD were also noted to have similar effects in other respiratory illnesses such as influenza 15 and H1N1. [16][17][18] In contrast, comorbidities such as immunodeficiency and HIV were reported to be in low prevalence in severe MERS-CoV cases (range: 0-5%) 1,3 compared, for example, to their rates in severe H1N1 cases (range: 3-32%). 16,19 Metabolic syndrome-related conditions such as diabetes, hypertension, CAD/CVD and obesity complications.…”
Section: Discussionmentioning
confidence: 74%
“…This study reported a significant association between overweight and CHIKV sequelae (OR = 1.3; 95% CI: 1.2-1.4) (Padmakumar et al, 2010). Chronic conditions influencing the severity of CHIKV such as diabetes were also noted to have similar effects in other respiratory illnesses (Badawi and Ryoo, 2016a, b;Mertz et al, 2013;Kusznierz et al, 2013). Furthermore, a number of case-control studies demonstrated the incidence of metabolic syndrome and related diseases, e.g., diabetes and hypertension, to be 2-fold higher in severe cases of dengue fever than in non-severe conditions (Fujimoto and Koifman, 2014;Pang et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Un estudio realizado en la ciudad de Santa Fe, Argentina, por Kusznierz y cols. 33 incluyó a 68 pacientes menores de 15 años hospitalizados por influenza pandémica. En este grupo de pacientes ninguno fue obeso.…”
Section: Enfermedad Respiratoria En Niños Chilenos: Incidencia Y Etiounclassified